Heideggers Zeit des Umbruchs: 90 Jahre Rigaer Vorträge - Bičevskis, Raivis; Seubert, Harald (Verlag Karl Alber, 2023)
In September 1928, Heidegger gave a series of lectures in Riga on Kant's "Critique of Pure Reason" and the philosophical problems of the present. A year later he published the book "Kant and the Problem of Metaphysics", which was of the greatest importance for the debate with Cassirer in Davos in 1929. In this book, distinguished Heidegger experts shed light on the period after the publication of "Being and Time", including the question of how Heidegger attempted to continue or transform fundamental ontological thought.